(untitled) (Jurnal Bahasa Lingua Scientia, 2024)
Teaching English to children with special needs in inclusive settings is a challenge that requires the cooperation and participation of all parts of the school. However, teaching English to students with special needs may sound strange or even impossible. Nevertheless, this is part of the responsibility of education to remain accepted as part of the challenges of the education world. The Purpose of this research is to know the used of method for teaching speaking in students with hearing impairment in one of SLB in Pasuruan and to know what the method that used in this SLB. The design of this study was descriptive qualitative. The subject of this study was 6 hearing impairment students in seventh grade and an English teacher of SLB Arya Satya Hati Pasuruan, which was conducted to investigate the use of methods for teaching speaking. The instruments used were observation, interview, and documentation. The findings showed that the teacher used a natural method, the grammatical method, the Bilingual-Bicultural Method (Bi-Bi), and targeted effective dissemination, mixing language combined with sign language and gesture. Drilling or repetition is the main method for making the teaching process achieves goals. Finally, it can be concluded that the teacher used various instructional methods for teaching speaking students with hearing impairment.